Foreign Bank Entry and Cost Efficiency of Asian banks: A Stochastic Frontier Approach - Ajageer, Vashisht Kumar (2012)
This dissertation is motivated by the remarkable efforts in the liberalisation of the Asian banking sector in recent years. Using bank level data for 43 countries during the period 2005 to 2011, this dissertation examines the impact of foreign banking entry on the efficiency level of domestic Asian banks. As such, a stochastic frontier analysis has been adopted to estimate translog cost function for the Asian banks. Moreover, this study has controlled for both heteroscedasticity and the influence of environmental variables on the banks cost efficiency. The findings suggest that foreign banks entry cause a decline in the efficiency level of the banks in the domestic sector. This puts into question International Financial Institutions’ recommendations made over the past decade to enhance the presence of foreign banks. Moreover, the domestic banks have been found to be more cost efficient than the foreign banks. The fact that Asia is a diverse region in terms of various income level countries has prompted this study to examine the efficiency level between developed and developing Asian countries. The findings indicate that the developed Asian countries are more efficient than the developing Asian countries. Amongst the 43 Asian countries, banks from Qatar are the most efficient while banks from Iraq are the least efficient.